Composite silicon-based negative electrode material, preparation method and solid-state battery

By introducing a composite structure of graphite matrix, silicon carbide nanowires and nanosilicon particles into the silicon-based anode material, the problems of poor cyclic stability and low safety of the silicon-based anode material are solved, and better mechanical properties and cyclic properties are achieved.

CN119890278AActive Publication Date: 2025-04-25安徽得壹能源科技有限公司 +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510368593.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have problems of poor cycle stability and low safety during the circulation process, mainly due to the solid-solid contact problem between lithium metal and sulfide solid electrolyte, large volume changes in lithium metal, growth of lithium dendrites, and side reactions of metal lithium/electrolyte interface.

Method used

A composite silicon-based negative electrode material is used, including graphite matrix, silicon carbide nanowires and nanosilicon particles. The silicon carbide nanowires form a network structure, and the nanosilicon particles are dispersed in the network structure, and the material is prepared by molten salt electrolysis.

Benefits of technology

The porous structure relieves the damage to the electrode structure by volume expansion, improves the mechanical properties of the silicon negative electrode, improves the cycling performance, and prevents the agglomeration of nano-silicon particles, ensuring good contact with the conductive material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890278A_ABST
    Figure CN119890278A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite silicon-based negative electrode materials, and discloses a composite silicon-based negative electrode material, a preparation method and a solid-state battery, the composite silicon-based negative electrode material comprises a graphite matrix, and silicon carbide nanowires and nano silicon particles attached to the surface of the graphite matrix, and the nano silicon particles are dispersed in the network structure. The nanometer silicon particles are dispersed in a network formed by interweaving the silicon carbide nanowires, and a porous structure similar to a reinforced concrete structure is presented; the porous structure can provide a space for volume expansion and alleviate the damage of volume expansion to the electrode structure in the silicon-based negative electrode lithium intercalation and deintercalation process, and meanwhile, the one-dimensional silicon carbide has relatively high mechanical strength, so that the damage of long circulation of the silicon negative electrode to the electrode structure can be relieved, and the mechanical property of the silicon negative electrode is improved; therefore, the cycle performance of the silicon electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite silicon-based negative electrode materials, and in particular relates to a composite silicon-based negative electrode material, a preparation method and a solid-state battery. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] With the rapid development of electric vehicles, distributed energy systems and smart grids, higher and higher requirements are placed on the energy density, life and safety performance of batteries. Compared with flammable organic liquid electrolytes, solid electrolytes have the advantages of higher thermal stability, non-flammability, no leakage and no volatility, and have a higher thermal runaway starting temperature, which is conducive to improving the safety and stability of batteries. While improving safety, the use of solid electrolytes makes it possible to use high-voltage positive electrode materials, thereby increasing the energy density of batteries.

[0004] In order to achieve high energy density all-solid-state batteries, the market has focused on metallic lithium and its alloy materials or silicon-based negative electrodes. When metallic lithium negative electrodes are used in sulfide solid-state batteries with ultra-high ionic conductivity and good plasticity, there are still problems of poor cycle stability and low safety. The fundamental reasons are the solid-solid contact problem between lithium metal and sulfide solid electrolyte, the large volume change of lithium metal during the cycle, the growth of lithium dendrites, and the side reactions at the metallic lithium / electrolyte interface.

[0005] Compared with graphite (0.1V) and lithium metal negative electrodes, which are unstable at the interface with sulfides, the lithium insertion potential of silicon is 0.4V, which can alleviate the interfacial side reactions to a certain extent while achieving a higher open circuit voltage. Combined with the high specific capacity of the silicon-based negative electrode, it is conducive to the realization of high energy density and high safety solid-state batteries. At the same time, the combination of silicon-based negative electrode and sulfide solid electrolyte can avoid the problem of repeated generation of solid electrolyte interface layer (SEI) of silicon-based negative electrode in liquid battery, give full play to the high capacity of silicon-based negative electrode, and use the better mechanical properties of sulfide to buffer the huge volume expansion of silicon negative electrode, improve solid-solid contact, promote ion diffusion, and is expected to achieve long-term circulation of high energy density batteries.

[0006] In order to improve the cycle performance of silicon negative electrode materials, one of the ways to improve the stability of silicon negative electrode is to nanosize silicon. Nanomaterials have the characteristics of large specific surface area, short ion diffusion path, strong creeping and high plasticity, which can alleviate the volume effect of silicon negative electrode materials to a certain extent and improve their electrochemical performance. However, nanomaterials are easy to agglomerate during the cycle process, which is not enough to improve the performance of the battery to practical use.

[0007] Another effective method is to prepare a silicon-containing composite material and utilize the synergistic effect between the components of the composite material to achieve the purpose of complementary advantages. For example, Jian (Journal of Power Sources, 2017, 342: 529-536) et al. prepared a core-shell structured silicon@C@void@C nanocomposite material, which can not only reduce the interface resistance but also effectively protect the structural stability of the silicon material. However, its preparation method is relatively complicated and not suitable for industrial production.

[0008] Others use etching methods to prepare silicon nanowires, and then use CVD methods to coat a layer of silicon C on the surface of the silicon nanowires to prepare silicon C-silicon nanowires. Finally, a layer of graphene with good conductivity is grown on the surface of silicon C-silicon to obtain Gr-silicon C-silicon nanowires with a sandwich structure. This material has a large first discharge capacity and good cycle performance, but the preparation method is complex and the preparation cost is high, which is not conducive to industrial production. In addition, the core-shell structured silicon@C@void@C nanocomposites and Gr-silicon C-silicon nanowires are both carbon coated on the surface of silicon particles, and silicon and solid electrolytes cannot contact each other, resulting in low ionic conductivity of silicon-based electrodes. Summary of the invention

[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite silicon-based negative electrode material, a preparation method and a solid-state battery.

[0010] In order to achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a composite silicon-based negative electrode material, comprising a graphite substrate and silicon carbide nanowires and nano-silicon particles attached to the surface of the graphite substrate, wherein the silicon carbide nanowires are interwoven to form a network structure, and the nano-silicon particles are dispersed in the network structure.

[0011] In some embodiments, the mass percentage of graphite in the composite silicon-based negative electrode material is 9.9%-25%.

[0012] In some embodiments, in the composite silicon-based negative electrode material, the mass percentage of nano silicon particles is 20%-90%.

[0013] Preferably, the particle size of the nano-silicon particles is 30-150 nm.

[0014] In some embodiments, in the composite silicon-based negative electrode material, the mass percentage of silicon carbide nanowires is 0.1%-5%.

[0015] Preferably, the diameter of the silicon carbide nanowires is 10-100 nm.

[0016] In a second aspect, the present invention provides a method for preparing the composite silicon-based negative electrode material, comprising the following steps: Nano-silicon dioxide, graphite and carbon powder are mixed in proportion and pressed into shape to obtain a precursor; the precursor is compounded with a current collector as a cathode, and molten salt is used as an electrolyte. Under an inert atmosphere, electrolysis is performed at a temperature greater than 500°C for a set time to obtain a composite silicon-based negative electrode material.

[0017] Carbon powder is the carbon source of silicon carbide; graphite is conductive and can be used as a carrier of nano-silicon. Molten salt melts at high temperature and acts as an electrolyte and a medium for conducting ions.

[0018] In some embodiments, the mass ratio of nano-silicon dioxide, graphite and carbon powder is 40-200:8-90:0.1-1.

[0019] Preferably, the mass ratio of nano-silicon dioxide, graphite and carbon powder is 40-90:50-80:0.5-1.

[0020] Further preferably, the mass ratio of nano-silicon dioxide, graphite and carbon powder is 40-90:50-80:0.8-1.

[0021] Preferably, the average particle size of the nano-silicon dioxide is less than 100 nm.

[0022] More preferably, the shape of the nano-silicon dioxide is spherical or quasi-spherical.

[0023] In some embodiments, the electrolyte is molten CaCl2, sodium chloride, potassium chloride, or lithium chloride.

[0024] In some embodiments, the electrolysis temperature is 500-1000° C., and the electrolysis time is 6-10 h.

[0025] In some embodiments, the voltage of electrolysis is lower than 3.0 V. When the voltage is greater than 3 V, the molten salt may be electrolyzed or other impurities may be generated.

[0026] Preferably, the voltage of electrolysis is 1-3V, preferably 2-3V.

[0027] In some embodiments, the step of washing the composite silicon-based negative electrode material prepared by electrolysis is further included, and the washing method is: soaking the composite silicon-based negative electrode material prepared by electrolysis in dilute hydrochloric acid, washing with water and washing with anhydrous ethanol in sequence, and then drying. Soaking in dilute hydrochloric acid, washing with water and washing with anhydrous ethanol in sequence is to remove molten salt.

[0028] In a third aspect, the present invention provides a solid silicon-based negative electrode, comprising a supporting conductive substrate and an active coating, wherein the active coating is coated on the supporting conductive substrate, and the active coating is a mixture of the composite silicon-based negative electrode material, an electrolyte, and a conductive agent.

[0029] In a fourth aspect, the present invention provides a solid-state battery comprising the solid-state silicon-based negative electrode.

[0030] The beneficial effects achieved by one or more embodiments of the present invention are as follows: The composite silicon-based negative electrode material of the present invention comprises graphite and silicon carbide nanowires and nano-silicon particles generated on the surface of the graphite, wherein the nano-silicon particles are dispersed in a network interwoven by the silicon carbide nanowires, presenting a porous structure similar to a reinforced concrete structure, and the porous structure can provide space for volume expansion, thereby slowing down the damage to the electrode structure caused by the volume expansion during the lithium insertion and extraction process of the silicon-based negative electrode, and at the same time, the one-dimensional silicon carbide therein can slow down the damage to the electrode structure caused by the long cycle of the silicon negative electrode due to its high mechanical strength, thereby improving the mechanical properties of the silicon negative electrode and thus improving the cycle performance of the silicon electrode.

[0031] In addition, in the composite silicon-based negative electrode material of the present invention, since nano-silicon carbide grows on the graphite surface, the nano-silicon particles are dispersed in the network formed by the nano-silicon carbide wires, which can effectively prevent the agglomeration of the nano-silicon particles and ensure good contact between the nano-silicon and the conductive material (graphite) during the lithium insertion and extraction process of the electrode.

[0032] The raw materials for preparing the composite silicon-based negative electrode material of the present invention are readily available, the equipment is cheap, the preparation method is simple, easy to operate and easy to industrialize, and no pollution is generated during the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 This is a microscopic morphology of the composite silicon-based negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] The present invention is described below in conjunction with the accompanying drawings and embodiments. These descriptions are only intended to further illustrate the present invention, rather than to limit the present invention.

[0037] Example 1 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 192.8:9.9:0.1, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor was compounded with the conductive cathode current collector as the cathode, the graphite rod was used as the anode, and molten CaCl2 was used as the electrolyte. In an argon environment, the temperature was 850°C, and the voltage was controlled by a potentiostat for constant voltage electrolysis. The cell voltage was 2.5V and the electrolysis time was 6h.

[0038] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0039] (2) Use a homogenizer to mix the composite silicon-based negative electrode material, sulfide electrolyte, and conductive agent in a mass ratio of 60:40:3 for 30 minutes, then coat the mixed slurry on copper foil, dry it at 100 °C for 3 hours, and punch out a sheet with a diameter of 9 mm; finally, assemble the solid-state battery and test its electrochemical performance. The microscopic morphology of the composite silicon-based negative electrode material, such as Figure 1 shown.

[0040] Example 2 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 171.4:19.5:0.5, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a potentiostat for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 7h.

[0041] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0042] (2) Use a homogenizer to evenly mix the composite silicon-based negative electrode material, sulfide electrolyte, and conductive agent in a mass ratio of 60:40:3 for 30 minutes. Then, the mixed slurry is coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, the solid-state battery is assembled and its electrochemical performance is tested.

[0043] Example 3 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 150:29:1, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a potentiostat for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 8h.

[0044] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0045] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0046] Example 4 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 128.6:39:1, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a voltage regulator for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 9h.

[0047] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0048] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0049] Example 5 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 107.1:49:1, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a potentiostat for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 10h.

[0050] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0051] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0052] Example 6 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 85.7:59:1, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, mixing them uniformly, and pressing them into a shape to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a potentiostat for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 10h.

[0053] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0054] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0055] Example 7 (1) weighing nano-silicon dioxide, graphite and cracked carbon in a mass ratio of 42.8:79:1, mixing them uniformly, wherein the average particle size of the nano-silicon dioxide is less than 100 nm, and pressing and molding to obtain a precursor; The precursor and the conductive cathode current collector are composited as the cathode, the graphite rod is used as the anode, and the molten CaCl2 is used as the electrolyte. In an argon environment, the temperature is 850°C, and the voltage is controlled by a potentiostat for constant voltage electrolysis. The cell voltage is 2.5V and the electrolysis time is 8h.

[0056] After the electrolysis is completed, the electrolysis product is sequentially soaked with dilute hydrochloric acid, filtered and cleaned with deionized water, filtered and cleaned with anhydrous ethanol, and vacuum dried to obtain a composite silicon-based negative electrode material.

[0057] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0058] Comparative Example 1 (1) Nano-silicon particles and graphite are weighed in a silicon-carbon mass ratio of 70:30, mixed evenly in a solvent, and dried with air to obtain a composite silicon-based negative electrode material.

[0059] (2) The composite silicon-based negative electrode material, sulfide electrolyte and conductive agent were uniformly mixed in a mass ratio of 60:40:3 for 30 min using a homogenizer. The mixed slurry was then coated on a copper foil, dried at 100 °C for 3 h, and punched into a sheet with a diameter of 9 mm. Finally, a solid-state battery was assembled and its electrochemical performance was tested.

[0060] Comparative Example 2 The difference from Example 6 is that the voltage of electrolysis is 3.1V, and the rest is the same as Example 6.

[0061] Comparative Example 3 The difference from Example 6 is that the cracked carbon in Example 6 is omitted, and the rest is the same as Example 6.

[0062] Table 1 Comparison of initial charge and discharge capacity of composite silicon-based solid-state anodes with different silicon contents

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite silicon-based negative electrode material, characterized in that: It comprises a graphite matrix and silicon carbide nanowires and nano-silicon particles attached to the surface of the graphite matrix, wherein the silicon carbide nanowires are interwoven to form a network structure, and the nano-silicon particles are dispersed in the network structure.

2. The composite silicon-based negative electrode material according to claim 1, characterized in that: In the composite silicon-based negative electrode material, the mass percentage of graphite is 9.9%-25%.

3. The composite silicon-based negative electrode material according to claim 1, characterized in that: In the composite silicon-based negative electrode material, the mass percentage of nano silicon particles is 20%-90%.

4. The composite silicon-based negative electrode material according to claim 1, characterized in that: In the composite silicon-based negative electrode material, the mass percentage of silicon carbide nanowires is 0.1%-5%.

5. The method for preparing the composite silicon-based negative electrode material according to any one of claims 1 to 4, characterized in that: The steps include: Nano-silicon dioxide, graphite and carbon powder are mixed in proportion and pressed into shape to obtain a precursor; the precursor is compounded with a current collector as a cathode, and molten salt is used as an electrolyte. Under an inert atmosphere, electrolysis is performed at a temperature greater than 500°C for a set time to obtain a composite silicon-based negative electrode material.

6. The method for preparing the composite silicon-based negative electrode material according to claim 5, characterized in that: The mass ratio of nano silicon dioxide, graphite and carbon powder is 40-200:8-90:0.1-1.

7. The method for preparing the composite silicon-based negative electrode material according to claim 6, characterized in that: The mass ratio of nano silicon dioxide, graphite and carbon powder is 40-90:50-80:0.5-1.

8. The method for preparing the composite silicon-based negative electrode material according to claim 5, characterized in that: The electrolyte is molten CaCl2, sodium chloride, potassium chloride or lithium chloride; the electrolysis temperature is 500-1000°C, the electrolysis time is 6-10h; and the electrolysis voltage is lower than 3.0V.

9. A solid silicon-based negative electrode, characterized in that: It comprises a supporting conductive substrate and an active coating, wherein the active coating is coated on the supporting conductive substrate, and the active coating is a mixture of the composite silicon-based negative electrode material, electrolyte and conductive agent as claimed in any one of claims 1 to 4.

10. A solid-state battery, characterized in that: It comprises the solid silicon-based negative electrode as described in claim 9.

Citation Information

Patent Citations

  • Nano silicon-carbon composite material and preparation method thereof

    CN103107315A

  • Nano silicon composite negative electrode material for lithium ion battery, preparation method and lithium ion battery

    CN104577084A

  • Apparatus for preparing nanometer silicon-carbon composite negative material through fused salt electrolysis, and method thereof

    CN104733702A

  • Method for preparing carbon nanotube / SiC / nano Si composite material, composite material and lithium ion battery

    CN106784695A

  • Si / SiC / C composite material and preparation method and lithium ion battery cathode and battery

    CN106784698A